Blood Profile and Heavy Metal Levels Among Gas Station Workers in Malang - Ari Prasetyadjati; Taufiq Abdullah; Munsifah Zaiyanah; Erka Wahyu Kinanda; Sabrina Analisa (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2026)
Fuel-station attendants are chronically exposed to lead, mercury and cadmium through inhalation of vehicle-exhaust particulates and dermal contact with fuel residues, placing them at elevated risk of cardiovascular and renal disease. Despite this recognised hazard, integrated health-surveillance data for Indonesian pump operators remain scarce. This study aimed to characterise the vascular status, haematological and biochemical profile, circulating heavy-metal concentrations and occupational safety behaviours of fuel-station workers in Malang, East Java. A descriptive cross-sectional design was employed. Twenty male pump attendants were recruited by census sampling from multiple SPBU outlets in Malang during 2025. Each participant underwent seated blood-pressure measurement, pulse oximetry and venous blood collection for quantification of lead, mercury, cadmium, renal function markers (ureum, creatinine, BUN), liver enzymes (SGOT, SGPT) and electrolytes. A structured interviewer-administered questionnaire captured sociodemographic data, smoking status and occupational safety practices. Hypertension was defined per the 2024 ESC Guidelines (≥140/90 mmHg) and metal concentrations were benchmarked against WHO occupational thresholds. Pearson correlation and SPSS 26 were used for analysis. Mean age was 26.8 ± 5.9 years. Eleven workers (55%) met the hypertension criterion (mean systolic 134.6 ± 13.9, diastolic 85.2 ± 8.8 mmHg). Blood lead averaged 30.22 ± 4.96 µg/L, exceeding the 20 µg/L occupational threshold in all 20 participants (100%). Mercury (16.32 ± 2.75 µg/L) and cadmium (3.44 ± 0.83 µg/L) mostly remained within limits. Renal and hepatic panels were largely unremarkable; however, employment duration correlated positively with blood lead (r = 0.45, p = 0.047) and with ureum (r = 0.50, p = 0.024). Only nine workers (45%) used masks or gloves routinely and six (30%) attended periodic health examinations. Universal lead-level elevation, high hypertension prevalence and poor protective-equipment compliance underscore the need for routine metal screening, cardiovascular surveillance and structured occupational-health programmes for Indonesia's fuel-station workforce.